2017
DOI: 10.1002/jso.24702
|View full text |Cite
|
Sign up to set email alerts
|

Is axillary surgery beneficial for patients with adenoid cystic carcinoma of the breast?

Abstract: We observed no cases of nodal metastasis in 20 consecutive cases of ACC of the breast. Preoperative axillary ultrasound with FNA of suspicious nodes accurately predicted pathologic nodal stage. These data suggest axillary surgery might be omitted safely in patients with pure ACC and a clinically negative axilla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Patients receiving lumpectomy and radiation therapy had a survival benefit of 9% at 5 years and 21% at 10 years. Therefore, radiotherapy decreases local recurrence for patients who had undergone BCT like in our case [ 3 , 6 , 8 , 10 ].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Patients receiving lumpectomy and radiation therapy had a survival benefit of 9% at 5 years and 21% at 10 years. Therefore, radiotherapy decreases local recurrence for patients who had undergone BCT like in our case [ 3 , 6 , 8 , 10 ].…”
Section: Discussionmentioning
confidence: 84%
“…Lymph node involvement is very rare (not exceeding 2%), however, SLNB is required for ACC, as with any invasive breast primary. In a retrospective case series from with follow up of 20 years, patients with pure ACC (n = 20), out of a 15,749 total cases of invasive breast cancer, 15 of those had SLNB with pathologically node-negative lymph nodes, and no evidence of any lymph node involvement in 20 year follow up [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study using the California cancer registry, 5% of patients had lymph node involvement (13). Even in other studies, none of the cases found axillary lymph node metastasis through sentinel lymph node biopsy or axillary lymph node dissection (3,5). Thus, some studies recommend that axillary surgery might be omitted safely in patients with pure ACC and a clinically negative axilla.…”
Section: Discussionmentioning
confidence: 99%
“…Adenoid cystic carcinoma (ACC) of the breast is a rare special histological type of breast cancer, accounting for approximately 0.1% of all breast tumors (1)(2)(3). Most cases are in females, and the median age of onset is between 50 and 60 years old (4,5). However, occasional cases have been reported in male patients (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning favourable prognoses and low probability of the presence of metastases in the lymph nodes (0-2%), doubts arise pertaining to the necessity for biopsy of the sentinel lymph node or axillary lymphadenectomy in patients with clinically and ultrasound suspicious nodes [14]. According to some researchers, such management is not recommended [15,16].…”
Section: Treatmentmentioning
confidence: 99%